Modeling and Analysis of Ecological Urban Landscape Pattern Evolution Based on Multisource Remote Sensing Data - Zhang Min; Wang Xuejie; Liu Yun (Complexity)
Considering that the development of urbanization cannot be separated from the application of landscape pattern evolution, in order to improve the development level of ecocity, a modeling analysis of ecological urban landscape pattern evolution based on multisource remote sensing data is proposed. Taking ecotype city as the research object, the remote sensing images of ecological urban landscape pattern are screened by using multisource remote sensing data and nonremote sensing data as the basic data. CA-Markov model is constructed and the evolution of ecological urban landscape pattern is analyzed. The experimental results show that, from 2005 to 2020, the development level of urbanization process is higher and higher and the area of building land patches is increasing, which reduces the fragmentation of building land patches. However, the landscape of cultivated land and green space is less and less, and the distribution of the patches also causes uneven phenomenon, which leads to the gradual decline of ecological urban landscape diversity. In the ecological urban landscape pattern, the degree of fragmentation and diversity of urban landscape is reduced due to the high connection and coverage of the construction land.